Haemodynamic and electrocardiographic accompaniments of resting postprandial angina. Issue 4 (October 1979) - Figueras, J; Singh, B N; Ganz, W; Swan, H J
Abstract : The early postprandial changes in 10 patients with angiographically proven coronary artery disease and history of postprandial angina were studied by the continuous recording on magnetic tape of the electrocardiogram and haemodynamic variables. The significant changes 20 minutes after a meal not followed by angina included increases in cardiac index and stroke index, with a decrease in systemic vascular resistance. When angina developed after a meal, there were significant increases in mean systemic arterial blood pressure, heart rate, pulmonary capillary wedge pressure, and systemic vascular resistance with decreases in stroke index at the onset of pain rather than at the onset of ischaemic electrocardiographic abnormalities. The first haemodynamic variable to change was pulmonary capillery wedge pressure which tended to increase coincident in time with the electrocardiographic abnormalities. In all cases, postprandial angina occurred within 25 minutes after a meal. In every instance, there was little or no change in the product of heart rate and systolic arterial blood pressure at the onset of the ischaemic electrocardiographic abnormalities at a time when the pulmonary capillary wedge pressure had begun to rise. Postprandial angina, like many cases of rest angina, may rise on the basis of a primary decrease in myocardial perfusion, the nature of which is unclear but merits further investigation.